Efficiency Analysis of the Banks Operating in Turkey with AHP based on DEA Method - Adem Babacan; Şahin Bulut; Neslihan Koç (Amfiteatru Economic)
In this study, performance and its basic concepts, efficiency, and productivity, are explained and performance measurement methods are discussed. The Analytical Hierarchy Process (AHP) was used to measure efficiency in multi-criteria problems and to determine the weights of criteria for efficiency measurement. With the help of the Data Envelopment Analysis (DEA), which is one of the best methods of measurement of efficiency, efficiency levels of the banks in Turkey, whose data can be fully reached, was evaluated. The criteria for bank efficiency were weighted with the AHP and then the efficiency scores of the banks were determined using the Weighted DEA method. Potential improvements have been proposed for inefficient banks.